Penerimaan Metaverse Dalam Percobaan Laboratorium yang diperbesar dan Virtual Belanja - Purnomo, Dhaniki (Universitas Serambi Mekkah, 2024)
This study aims to analyze the impact of using Augmented Reality (AR) and Virtual Reality (VR) technologies on consumer shopping experiences in the metaverse, focusing on the variables of Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment, Attitude, and Intention to Visit. Utilizing a quantitative method with a questionnaire distributed to 102 respondents aged 18-35 years, the study found that the use of AR and VR significantly influences Perceived Usefulness and Perceived Ease of Use, which subsequently affect Attitude and Intention to Visit. Furthermore, Perceived Enjoyment was identified as a factor that strengthens the relationship between AR/VR technologies and Attitude, contributing to increased intentions to visit metaverse stores. These findings highlight the importance of integrating AR and VR technologies into digital marketing strategies and provide insights for companies in designing immersive and engaging shopping experiences on metaverse platforms. The study offers implications for retailers to leverage AR and VR to enhance consumer satisfaction and visitation intentions.